A study On The Halal Food Supply Chain Using 3 Countries Perspective - Fadila Nurfauzia; Destiana Ayuningtyas Zahra (SINTESA, 2023)
Halal food supply chain is one of the things that is being highlighted in various parts of the world based on a report from the Global Islamic Economy. All of the questions regarding the core of this research focused on finding out the system halal food supply chain of Japan and Malaysia and comparing both with the system halal food supply chain of Indonesia. Indonesia is one of the largest Islamic countries in the world, while the system in halal food in Indonesia is the halal certification system issued by the MUI. Halal certification of a food production facility, food product, or slaughterhouse is an examination of the people, practices, and products that comply with Islamic laws by a competent organization. The Malaysian Islamic Development Department, abbreviated as (JAKIM), is the Malaysian government agency that regulates Islamic religious affairs in Malaysia. the halal process in Japan, it is based on the system carried out by Malaysia, the Japanese government collaborated and adopted the system for implementing halal certificates in Malaysia. Some halal institutions in Japan can have ties with the existing system in Malaysia as shown in the picture above. For example JIT has obtained mutual certification from Malaysia (JAKIM). There are several halal certificate organizations in Japan such as the Japan Muslim Association, Japan Halal Association, Kyoto Halal Council etc. The aim of this research, is to analyse three perspective about halal supply chain management in Indonesia, Japan and Malaysia. Indonesia have different system of halal supply chain between Japan and Malaysia. The result of this research is analyse and compare best system of halal supply chain